ENHANCING PERFORMANCE: TRAINING, DEVELOPMENT, AND ISLAMIC CULTURE'S IMPACT ON BMT EMPLOYEE PRODUCTIVITY - Prakoso, Agung Suryo; Rijal, Muhammad Saifur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to analyze the influence of employee training, employee development, and Islamic organizational culture on employee productivity through job satisfaction among employees of Baitul Maal wa Tamwil (BMT) in East Java. This research employs a quantitative approach using a survey method. The population of this study comprises all BMT employees in East Java, with a sample size of 200 employees selected through purposive sampling. Data analysis techniques include Structural Equation Modeling (SEM) to test the relationships between variables. The results indicate that employee training, employee development, and Islamic organizational culture have a positive and significant impact on job satisfaction. Furthermore, job satisfaction positively and significantly affects employee productivity. Hence, job satisfaction is proven to be an effective mediator between employee training, employee development, Islamic organizational culture, and employee productivity. The conclusion of this study is that efforts to enhance employee training and development, along with the implementation of a strong Islamic organizational culture, can increase job satisfaction and employee productivity in BMTs in East Java.